Enhanced biomechanical and biological performance of titanium scaffolds with gradient in pore sizes - Ara Jung; Jinju Jang; Hun Yeong Ban; Hee Jin Kim; Bomi Gweon; Dohyung Lim (Journal of Materials Research and Technology)
With the rapid advancement of metal 3D printing technologies, porous metal implants are increasingly explored for regenerative medicine. Among various methods, powder bed fusion (PBF) stands out for its precision in implant design and fabrication. This study systematically investigates the structural, mechanical, and biological aspects of titanium scaffolds using PBF technology with varying pore sizes (400 μm, 600 μm, 800 μm, and 1000 μm). Micro-CT cross-sectional images revealed slight deviations in pore size and structure thickness from the intended designs, yet the overall structure adhered closely to specifications. Mechanical testing showed that as pore size increased, both the elastic modulus and yield strength decreased, with scaffolds in the 600–1000 μm range resembling the properties of human cortical bone. Osteoblast proliferation and differentiation were most active in scaffolds with 1000 μm pores, whereas endothelial cell proliferation thrived in 400 μm pores. To simultaneously enhance mechanical properties, osteointegration, and vascularization, scaffolds with a gradient in pore sizes from 400 μm to 1000 μm were designed and evaluated. These graded scaffolds demonstrated mechanical properties comparable to human cortical bone. In vitro experiments further supported the advantages of pore-size gradients, revealing accelerated osteoblast and endothelial proliferation in the Type 2 gradient scaffolds, featuring a gradient from the center (1000 μm) to the periphery (400 μm). Collectively, these findings suggest that the design strategy of the Type 2 gradient scaffold is beneficial not only for achieving biomechanical compatibility by closely mimicking natural bone but also for promoting osteogenesis and neovascularization.